(untitled) (Psychology Travelogs, 2025)
The article is devoted to the issue of psychological support for future managers during stress and the search for effective tools to overcome it. It discusses the characteristics of stress in the professional activities of managers and the main groups of factors that determine the development of stress responses in management activities. Special attention is given to the characteristics of professional stress in the field of management, which manifest in high responsibility, the need to coordinate the work of others, make complex decisions in conditions of uncertainty, and resolve conflicts within the team. The article examines the use of mindfulness techniques to reduce stress, improve emotional intelligence, decision-making, and strengthen psychological resilience in future managers. Mindfulness is a psychological approach at the intersection of psychology and neurophysiology that studies meditation as a practice of awareness, focusing on the present moment without judgment or evaluation. Techniques of conscious perception and attention contribute to reducing stress levels, overcoming anxiety and negative emotions, and improving the ability to make balanced decisions in high-pressure and uncertain conditions. This makes mindfulness an important tool for developing effective managers. The article describes the results of an empirical study of the psychological characteristics of future managers during stress. It analyzes the results of diagnostics of the distribution of stress levels among future managers. The results of the study on the distribution of post-traumatic growth indices in future managers with low and high levels of stress are presented. The article also analyzes the results of diagnostics of post-traumatic growth characteristics in future managers with low and high stress levels. A program of psychological support for future managers during stress using mindfulness techniques is described.